Colorado wildlife action plan enhancement: climate change vulnerability assessment - Fink, Michelle, author; Decker, Karin, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2014)
During the revision of Colorado's current SWAP, the Colorado Natural Heritage Program (CNHP), Colorado Parks and Wildlife (CPW), North Central Climate Science Center and U.S. Geological Service Fort Collins Research Center collaborated to produce climate change vulnerability assessments for high priority wildlife habitats in the state. Our objectives were to: 1. Evaluate exposure and sensitivity of priority habitats by identifying the degree of climate change expected between current and future conditions for climate factors believed to influence the distribution of the habitat. 2. Evaluate adaptive capacity of each habitat by assessing factors that affect the resilience of the habitat to change in landscape condition, invasive or problematic native species presence, dynamic process alteration between past and current conditions, and the characteristic bioclimatic envelope of the habitat. 3. Produce summary vulnerability ratings for priority habitats.
December 2014.
Keywords: potential impact; sensitivity; exposure; adaptive capacity; vulnerability